Percepții ale securității vecinătății în România post-revoluționară 1990-1992 - Keil, Thomas J.; Fenn, Jeanne M.; Tatu, Mădălina (Calitatea Vieții, 1994)
Using national probability surveys from 1990, 1991, and 1992, we have examined the factors associated with Romanians’ perceptions of neighbourhood safety in each of three years. Across the three years, urban residential location, satisfaction with one’s household, and satisfaction with the quality of relations with one’s neighbours had consistent effects on perceptions of neighbourhood safety. In 1990 and 1991, working class status and gender had effects on perceptions of neighbourhood safety.